Cheese and microbes - Donnelly, Catherine W. (ASM Press, 2014)
A scientific overview of the association of microbes with cheese, through the lens of select cheese varieties that result due to surface mold ripening, internal mold ripening, rind washing, cave aging, or surface smear rind development.